The Johannine footwashing as the sign of perfect love an exegetical study of John 13:1-20 - Mathew, Bincy 1979- (Tübingen Mohr Siebeck, 2018)
Cover -- Titel -- Acknowledgements -- Table of Contents -- Abbreviations -- General Introduction -- Chapter 1: The Footwashing: A Status Quaestionis -- A) The Footwashing: Non-Sacramental Interpretations -- I. The Footwashing as the Salvific Death of Jesus -- 1. Alan Culpepper (1991) -- 2. Marianne M. Thompson (2003) -- II. The Footwashing as the Vicarious or Atoning Death of Jesus -- 1. David Gibson (2007) -- 2. Otfried Hofius (2009) -- 3. Mark Matson (2014) -- B) The Footwashing: Sacramental Interpretations -- I. Francis J. Moloney (1991) -- II. Christopher Thomas (1991) -- C) Conclusion -- Chapter 2: "Except for the feet" John 13:10: A Text-Critical Analysis -- A) Variant Readings of John 13:10 -- B) External Criticism -- C) Internal Criticism -- I. Transcriptional Probability -- 1. Long Reading: The More Difficult Reading -- a) Are λούω and νίπτω Synonyms? -- (i) Leviticus 15:11 -- (ii) Tobit 7:9 -- (iii) Philo, De somniis -- (iv) Testament of Levi 9:11-12 -- (v) Aramaic Levi Document 19-25b -- (vi) Papyri Oxyrhynchus 840 -- (vii) Archaeological Evidence -- 2. The Long Reading Easily Explains Other Variations -- II. Intrinsic Probability -- 1. The Johannine Use of λούω and νίπτω -- 2. The Long Reading: A Grammatical Consideration -- D) Conclusion -- Chapter 3: "Ah, Yes! to Generous Souls How Noble Every Task!": Footwashing in the Ancient Jewish, Greek, and Roman Literature -- A) Previous Research on John 13 in Relation to Ancient Footwashing -- B) Footwashing in the Jewish Culture -- I. Washing One's Own Feet -- 1. Hygiene, Comfort and Hospitality -- a) Genesis 19:2 -- b) Genesis 24:32 -- c) Genesis 43:24 -- d) Judges 19:21 -- e) 2 Samuel 11:8 -- f) Canticles 5:3 -- 2. Ritual Setting -- II. Washing Someone Else's Feet -- 1. An Expression of Hospitality -- a) Genesis 18:4 -- b) Testament of Abraham -- c) 1 Timothy 5:10
2. An Expression of Intimacy and Love -- a) 1 Samuel 25:41 -- b) Joseph and Aseneth -- c) Luke 7:44 -- d) John 12:1-8 -- III. Metaphorical Footwashing -- 1. Psalm 57:11 (58:11 MT) -- 2. Psalm 59:10 (60:10 MT) -- Psalm 107:10 (108:10 MT) -- 3. Isaiah 49:23 -- C) Footwashing in Ancient Greek Culture -- I. Washing One's Own Feet -- 1. Hygiene and Comfort -- 2. Ritual Purpose -- 3. Metaphorical Footwashing -- II. Washing Someone Else's Feet -- 1. An Expression of Hospitality -- 2. Metaphorical Footwashing -- 3. Footwashing and Slavery -- 4. Footwashing in Banquet Settings -- D) Footwashing in Ancient Roman Culture -- I. Washing One's Own Feet -- 1. Hygiene and Comfort -- 2. Ritual Settings -- II. Washing Someone Else's Feet -- 1. An Expression of Intimacy and Love -- 2. Footwashing in Banquet Settings -- E) John 13 and the Footwashing Parallels -- Chapter 4: "Before the Feast of the Passover" The Structure and the Role of John 13:1-20 in Its Context -- A) The Structure of John 13:1-38 -- I. Discourse Development Markers -- II. Temporal Markers -- III. The Dramatis Personae -- IV. The Chiastic Structure -- 1. Peter's Objection as the Centre of Chiasm (John 13:1-35) -- 2. The Example of Jesus as the Centre of Chiasm (John 13:1-32) -- 3. Theme of Betrayal as the Centre of Chiasm (John 13:1-38) -- 4. The Commitment to Jesus (John 13:1-38) -- 5. Several Distinct yet Connected Units -- V. Inclusio in John 13:1-38 -- VI. John 13:1-20: The First Sub-Unit -- B) John 13:1-20 in Relation to Chapters 1-12 -- I. The Passover -- II. The Hour -- III. Fulfilment of the Scripture -- IV. The Dramatis Personae -- V. Action-Dialogue-Monologue Pattern -- C) John 13 in Relation to Chapters 14-17 -- I. Literary Structure -- II. The Literary Genre of John 13-17 -- 1. Jewish Farewell Discourse -- 2. Greek and Roman Farewell Discourse -- 3. The Greek Symposium -- D) Conclusion
Chapter 5: "I am Among You as One Who Serves" A Literary-Critical Analysis of John 13:1-20 -- A) A Critical Appraisal of Literary-Criticism on John 13 -- I. Oral Tradition -- II. Written Tradition(s) Theory -- 1. Theory of Multiple Traditions -- a) Marie-Émile Boismard -- b) Georg Richter -- c) Robert Fortna -- d) Christoph Niemand -- e) Urban C. von Wahlde -- 2. Theory of A Single Tradition -- a) Rudolf Bultmann -- b) Hartwig Thyen -- c) Raymond E. Brown -- III. The Synoptics' Influence on John 13 -- 1. Independence of John 13 from the Synoptics -- a) Raymond E. Brown -- b) Rudolf Schnackenburg -- 2. Dependence of John 13 on the Synoptics -- a) C. K. Barrett -- b) Maurits Sabbe -- (i) The Last Supper in the Synoptics -- (ii) John 13 and the Anointing Narratives -- 3. A Homogenous Composition? -- B) A Literary-Critical Analysis of John 13:1-20 -- I. The Johannine Narrative Introductions (John 13:1-3) -- II. The Presence of Satan in the Last Supper -- III. The Departure of Judas (John 13:30) -- IV. Jesus, the Serving Master (John 13:4-5) -- V. The Saying in John 13:16 -- 1. A Debate over John's Influence of Matthew 10 -- 2. John 13:16 and Matthew 10:24-25a: An Analysis -- VI. The Saying in John 13:20 -- 1. John's Use of ὁ λαμβάνων Instead of ὁ δεχόμενος -- 2. The Use of πέμπω for ἀποστέλλω -- 3. The Use of Indefinite τινα for the Definite ὑμεῖς -- C) Conclusion -- Chapter 6: "He Loved Them Perfectly" The Identity and Mission of Jesus and the Disciples (John 13:1-A, 20-A') -- A) The Identity and Mission of Jesus, John 13:1 (A) -- I. The Question of the Syntax of John 13:1 -- 1. John 13:1 in Previous Research -- a) Πρὸ δὲ τῆς ἑορτῆς τοῦ πάσχα neither Qualifies εἰδώς nor ἠγάπησεν (NIV) -- b) πρὸ δὲ τῆς ἑορτῆς τοῦ πάσχα Qualifies εἰδώς (NRSV) -- c) πρὸ δὲ τῆς ἑορτῆς τοῦ πάσχα Qualifies ἠγάπησεν (RSV)
d) πρὸ δὲ τῆς ἑορτῆς τοῦ πάσχα Qualifies both εἰδώς and ἠγάπησεν -- 2. A New Proposal for the Syntactic Structure of John 13:1 -- a) Arguments against the Three-Sentence Structure -- (i) John 13:2-5 -- (ii) John 19:28 -- (iii) John 13:1 -- b) Arguments against the Two-Sentence Structure -- c) Arguments in Favour of the One-sentence Structure -- 3. A New Translation for John 13:1 -- II. The Temporal Reference -- III. The Knowledge of Jesus -- IV. The Hour of Jesus -- 1. The Verb μεταβαίνω -- 2. The Prepositional Phrase ἐκ τοῦ κόσμου τούτου -- 3. The Johannine Use of πρὸς τὸν πατέρα -- V. The Love of Jesus for His Own -- VI. The Ultimate Manifestation of Love of Jesus -- 1. The Meaning of εἰς τέλος -- 2. The Final Act of Love of Jesus -- B) The Identity and Mission of 'His Own,' John 13:20 (A') -- I. The Receiver of the One Sent by Jesus -- 1. The Receivers of Disciples -- 2. The One Sent by Jesus -- II. The Father, the Centre of Mission -- C) Conclusion -- Chapter 7: "I know Whom I Have Chosen" Judas and Jesus: Breaching and Bridging the Code of Table Fellowship (John 13:2-B, 13:18-19-B') -- A) Love Is Denied, John 13:2 (B) -- I. An Ascensive καί -- II. The Genitive Absolute Construction -- III. The Progressing Supper -- IV. The Character Judas -- V. Whose Heart Is Involved? -- VI. The Name Ἰούδας Σίμωνος Ἰσκαριώτου -- VII. ἵνα παραδοῖ -- B) Love Is Affirmed, John 13:18-19 (B') -- I. Οὐ περὶ πάντων ὑμῶν λέγω -- II. ἐγὼ οἶδα τίνας ἐξελεξάμην -- III. The Old Testament Saying in John 13:18 -- 1. The Noun τρώγω -- 2. The Phrase μου τὸν ἄρτον -- 3. The Johannine ἐπαίρω -- 4. The Johannine πτέρνα -- IV. John 13:18,21 and Mark 14:18, 21 (Matthew 26:21 -- Luke 22:21) -- V. Believing Jesus as ἐγώ εἰμι (John 13:19) -- 1. The Verb πιστεύω in John -- 2. The Johannine ἐγώ εἰμι in 13:19 -- a) The ἐγώ εἰμι with Implicit or Explicit Predicate Compliment
b) The Absolute ἐγώ εἰμι -- VI. Love for Enemy in John? -- C) Conclusion -- Chapter 8: "If You Know ... If You Do" The Authority of the One Who Washes the Feet (John 13:3-C, 16-17-C') -- A) The Authority of Jesus, John 13:3 (C) -- I. ὅτι πάντα ἔδωκεν αὐτῷ ὁ πατὴρ εἰς τὰς χεῖρας -- II. Jesus' Origin and Destiny -- B) Authority of the Master and the Sender, John 13:16-17 (C') -- I. ἀμὴν ἀμὴν λέγω ὑμῖν -- II. οὐκ ἔστιν δοῦλος μείζων τοῦ κυρίου αὐτοῦ -- 1. The Comparative οὐκ ἔστιν μείζων -- 2. The First Components of the Comparison, δοῦλος and κύριος -- 3. The Second Components of Comparison, ἀπόστολος and ὁ πέμψας -- III. Blessedness of the One Who Does -- 1. The Adjective μακάριος -- 2. The Conditional Clauses -- 3. Correlation between Knowing and Doing -- C) Conclusion -- Chapter 9: "I Have Given You a Sign." Jesus' ὑπόδειγμα: The Gift and Task for the Disciples (John 13:4-11-D, 12-15-D') -- A) The Footwashing, Jesus' Gift of Life-Giving Love, 13:4-11 (D) -- I. Preparation for the Act of Love -- II. Washing the Feet Proper -- 1. εἶτα βάλλει ὕδωρ εἰς τὸν νιπτῆρα -- 2. Water in John 13 -- III. καὶ ἤρξατο νίπτειν τοὺς πόδας τῶν μαϑητῶν -- IV. καὶ ἐκμάσσειν τῷ λεντίῳ ᾧ ἦν διεζωσμένος -- V. The Misunderstood Identity of Jesus -- VI. ὃ ἐγὼ ποιῶ σὺ οὐκ οἶδας ἄρτι, γνώσῃ δὲ μετὰ ταῦτα -- VII. The Effect of the Action -- 1. οὐ μὴ νίψῃς μου τοὺς πόδας εἰς τὸν αἰῶνα -- 2. ἐὰν μὴ νίψω σε, οὐκ ἔχεις μέρος μετ᾽ἐμοῦ -- a) μέρος μετ᾽ἐμοῦ -- b) The Present Indicative ἔχεις -- VIII. Misunderstanding Peter -- 1. A Curious Peter in John 13:24 -- 2. Cowardly Love of Peter in John 13:36-38 -- 3. Status and Role: Seeing Peter through Another Prism -- IX. καὶ ὑμεῖς καϑαροί ἐστε, ἀλλ᾽ οὐχὶ πάντες -- X. The Parenthesis -- B) The Footwashing: The Task for Life-giving Love, John 13:12-15 (D') -- I. Completing the Action -- 1. γινώσκετε, Imperative or Interrogative?
2. νίπτειν τοὺς πόδας as Jesus' Doing
Keywords: Hochschulschrift